2011
DOI: 10.1371/journal.pone.0021629
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Fusarium boothii Mycovirus via Protoplast Fusion Causes Hypovirulence in Other Phytopathogenic Fungi

Abstract: There is increasing concern regarding the use of fungicides to control plant diseases, whereby interest has increased in the biological control of phytopathogenic fungi by the application of hypovirulent mycoviruses as a possible alternative to fungicides. Transmission of hypovirulence-associated double-stranded RNA (dsRNA) viruses between mycelia, however, is prevented by the vegetative incompatibility barrier that often exists between different species or strains of filamentous fungi. We determined whether p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 42 publications
1
65
0
Order By: Relevance
“…Some hypovirulence-associated mycoviruses from B. cinerea and its related species Botrytis porri have been isolated and characterized (10,54,57), but these Botrytis viruses are unlikely to be used for control of diseases caused by these fungi under field conditions because they are easy to be eliminated via asexual propagation (see below). Expansion of the host range of mycoviruses has been accomplished for many fungus-mycovirus systems (7,8,24,(58)(59)(60)). …”
Section: Discussionmentioning
confidence: 99%
“…Some hypovirulence-associated mycoviruses from B. cinerea and its related species Botrytis porri have been isolated and characterized (10,54,57), but these Botrytis viruses are unlikely to be used for control of diseases caused by these fungi under field conditions because they are easy to be eliminated via asexual propagation (see below). Expansion of the host range of mycoviruses has been accomplished for many fungus-mycovirus systems (7,8,24,(58)(59)(60)). …”
Section: Discussionmentioning
confidence: 99%
“…In our study, the isolates growing at osmotic potential medium of -0.6 MPa and -1.8 MPa also showed a reduction of the mycelial growth. However, in the virus-infected Fusarium oxysporum strains when growing on PDA only slight morphological alterations were evident (Lee et al, 2011). Furthermore, it has been observed that Effect of mitovirus on mycelial growth of Gremmeniella abietina several Cryphonectria parasitica virus-infected strains grow as well as virus free isolates on most artificial media although they are incapable of producing grilling cankers on chestnut trees and sporulate poorly (McCabe et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…All strains used in this study (Table 1) were stored in 25% (vol/vol) glycerol at Ϫ80°C and were reactivated on potato dextrose agar (PDA; Difco). For nucleic acid manipulation, all strains of F. graminearum were grown in 50 ml of a liquid complete medium (CM) (29) at 25°C with shaking (150 rpm) for 5 days, while strains of C. parasitica were grown in 50 ml of Endothia parasitica complete medium (29) at 26°C with shaking (120 rpm) for 5 days. Mycelia were harvested by filtration through miracloth (Calbiochem) and ground to a fine powder with liquid nitrogen in a mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%
“…For extraction of genomic DNA, we used a previously described procedure (29). To construct a PCR fragment for deletion, overexpression, and complementation, a slightly modified double-joint (DJ) PCR strategy was applied for fusion of PCR products (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation